Planning Of 4A-Based Tourism Packages in Buahan Village, Payangan, Gianyar - Florenza Angeli Nazaretha Aling; Gusti Ngurah Yoga Semadi (International Journal of Economics, Management and Accounting, 2023)
Buahan Village, Payangan District, Gianyar Regency is a village that has the potential to become a tourist village with its attractions. However, this potential is not balanced with public awareness to develop tourism in their area. This research focuses on identifying potential through 4A theory, namelyAttraction, Accessibility, Amenities, and Ancillary. The results of this identification will result in the development of a tourist village by making tour packages according to the existing potential. To achieve the successful development of Buahan Village as a tourist village, awareness from the community is needed to manage tourism which will be carried out in a sustainable manner.